The relationship of green accounting to the dimensions of sustainable accounting and its impact on improving financial performance: An exploratory study of the opinions of a sample of workers in industrial companies in Sulaymaniyah Governorate." - کمال مصطفى, أڤریست; على أحمد, رزگار (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This research aims to know the extent to which green accounting contributes to achieving sustainable development and its reflection on improving financial performance. Green accounting is based on traditional accounting, taking into account environmental factors by calculating the costs of Environmental for the companies. This is because green accounting is the means by which it is possible to judge the extent of the institutions' commitment to preserving the environment, with the information it provides on the environmental costs incurred by the institution in this field. And that the research problem is that there is no appropriate ground for the success of the application of green accounting and ensuring its effectiveness through accounting guidelines and standards and reports on accounting to be adopted, regulations, there is no laws and precise standards that guarantee the reduction of pollution to organize work in economic units. As for the field aspect, it depends on the questionnaire form as a basic tool for obtaining information, through a statistical study that took a sample of the number of employees, experts and graduate certificates in some industrial companies in the Sulaymaniyah Governorate. Choosing a sample of 134 individuals, through which a set of conclusions are reached, the most important of which are: The need for green accounting is an effective tool for beneficiaries and decision makers with accounting information related to the costs of environmental performance and the preservation of the work environment from pollution. However, there are some shortcomings in green accounting, such as the problem of critical assessment of some environmental aspects and how to control them. The environmental dimension during the exercise of its activities, however, the environmental costs that can be measured financially separately are not disclosed in the financial statements, most of the specialists’ opinions towards the necessity of applying green accounting and integrating environmental costs within the financial statements within the indirect costs. The field study proved, through statistical analysis and specialists, that there is a statistically significant relationship between green accounting and sustainable accounting dimensions, which is a good relationship, and there is also a statistically significant relationship between green accounting and improving financial performance, but the reflection of green accounting on improving financial performance is not a relationship. Strong and the reason is due to some companies that did not apply green accounting and did not allocate large amounts of costs and purchase machinery and equipment to reduce environmental damage and to comply with international standards for this reason, we find through data analysis that the relationship is weak between green accounting and improving financial and environmental performance. In the recommendations, we can clarify that it is necessary to apply green accounting in industrial enterprises and to include environmental costs in the financial statements and their disclosure, that is, financial accounting is not separated from green accounting. This calls for strict international and national decisions about economic, social and environmental policies.